The effect of using the absolute training intensity equation to ration the intensity of the training unit for the stage of special preparation to develop some functional and skillful abilities of volleyball players (Journal of the College of Basic Education, 2022)
The study aimed to identify the impact of the training program for the development of some functional skills and capacity according to the equation training absolute density. The researcher used the experimental method for suitability to the nature of the research, the research sample consisted of (16) as a player and aged (16-18) years since, the research sample was divided into two groups and the control group and the experimental group of (8) players per group. The training program applied to the experimental group of (10) weeks and by (4) training modules in the week as a total of 40 training modules, and reached 120 module minute time either exercises used, prepared by the researcher in the experimental curriculum time, reaching for implementation 30 - 85 minutes. Taking into account the strict regulation of work and rest times of rationing module intensity through training density equation used by the researcher, and after the completion of the application of the training program was conducted a posteriori tests on the sample. And using appropriate statistical methods, the researcher to several conclusions, including that the training using the equation of absolute intensity training the experimental group had achieved remarkable development in all tests Search capabilities of physical, functional and technical skills for the tests before and after. But in the post tests dimensional experimental group has outperformed the control group in all tests except the search in only two tests are Alphusvegeneh test capacity and test beating overwhelming. The researcher recommends the need to legalize the use of training load using the equation density in training for volleyball players and mainstream way rationing training load using the equation in determining the severity of the module.